MicroVision dataset - Rasch, Alexander (Chalmers University of Technology, 2026)
This repository contains the MicroVision dataset: anonymized images and annotations of vulnerable road users and micromobility vehicles in real traffic (pedestrians, bicycles, cyclists, e-scooters, and e-scooterists). We further provide some first benchmark object-detection model weights (YOLO11, Faster R-CNN, and RF-DETR).

Det här arkivet innehåller MicroVision-datasetet: anonymiserade bilder och annoteringar av utsatta trafikanter och mikromobilitetsfordon i verklig trafik (fotgängare, cyklar, cyklister, elscootrar och elscooterförare). Vi tillhandahåller dessutom några första benchmark-vikter för objektigenkänningsmodeller (YOLO11, Faster R-CNN och RF-DETR).
MicroVision dataset
Keywords: kick scooters; sparkcyklar; pedestrian and bicycle ways; gång- och cykelbanor; traffic safety; trafiksäkerhet; image analysis; bildanalys; bicycles; cyklar; visual recordings; videogram; pedestrians; fotgängare; automated pattern recognition; mönsterigenkänning (teknik); annotations; images; transportation; Transport Systems and Logistics; Transportteknik och logistik; Vehicle and Aerospace Engineering; Farkost och rymdteknik; Computer Vision and learning System; Datorseende och lärande system